An exploratory study on the management of food waste through meaningful brands: A Starke Ayres case study - Wakeford (nee Louwrens), Melisca (The IIE, 2022)
Food waste is a rising global concern and impacts all people and the environment. It is crucial to address the issue of food waste to ensure a sustainable future with enough food to meet the ever-increasing food demand in the world. There are many food waste management techniques in use, but prevention is always better than cure. The F1 hybrid seeds produced by Starke Ayres, are a preventative solution to food waste as these hybrids have better disease resistance, fruit quality, and longer shelf life. However, the consumer does not understand what F1 hybrid seeds are and how it benefits the consumer and the environment. The researcher wanted to explore to what extent the brand can be described as meaningful and healthy and found that even though the brand has a strong purpose and offers products that are considered meaningful, it does not translate to the consumer. The researcher wanted to understand why the miscommunication between the brand and its consumer is happening and identify possible solutions for the brand to be truly meaningful and healthy. This study conforms to the applied research purpose and aims to uncover a practical solution for the Starke Ayres brand. The research was conducted using the interpretivism paradigm with an exploratory nature. The research for this study was conducted through three semi-structured in-depth interviews to gain a thorough and subjective understanding of the consumer’s perceptions and behaviours in relation to food waste and the brand’s solution, F1 hybrid seeds. The data were analysed using a thematic analysis approach to uncover themes and commonalities in the participant’s responses. The findings of this study indicate that the brand lacks effective communication with the consumer. This study assists the brand to implement better communication strategies to educate the consumer and ultimately reduce or prevent food waste at all levels.
Keywords: Healthy brands; Consumer behavior; Social media; GMO; Sustainability